Biomedical microfluidic devices by using low-cost fabrication techniques: A review. Issue 11 (26th July 2016) - Faustino, Vera; Catarino, Susana O.; Lima, Rui; Minas, Graça
Abstract: One of the most popular methods to fabricate biomedical microfluidic devices is by using a soft-lithography technique. However, the fabrication of the moulds to produce microfluidic devices, such as SU-8 moulds, usually requires a cleanroom environment that can be quite costly. Therefore, many efforts have been made to develop low-cost alternatives for the fabrication of microstructures, avoiding the use of cleanroom facilities. Recently, low-cost techniques without cleanroom facilities that feature aspect ratios more than 20, for fabricating those SU-8 moulds have been gaining popularity among biomedical research community. In those techniques, Ultraviolet (UV) exposure equipment, commonly used in the Printed Circuit Board (PCB) industry, replaces the more expensive and less available Mask Aligner that has been used in the last 15 years for SU-8 patterning. Alternatively, non-lithographic low-cost techniques, due to their ability for large-scale production, have increased the interest of the industrial and research community to develop simple, rapid and low-cost microfluidic structures. These alternative techniques include Print and Peel methods (PAP), laserjet, solid ink, cutting plotters or micromilling, that use equipment available in almost all laboratories and offices. An example is the xurography technique that uses a cutting plotter machine and adhesive vinyl films to generate the master moulds to fabricate microfluidic channels. In this review, we present a selection of the most recent lithographic and non-lithographic low-cost techniques to fabricate microfluidic structures, focused on the features and limitations of each technique. Only microfabrication methods that do not require the use of cleanrooms are considered. Additionally, potential applications of these microfluidic devices in biomedical engineering are presented with some illustrative examples.